Sea Food Export in Tamilnadu: A Case Study - Rajamohan, S; Jebadurai, D. Joel (Journal of Commerce and Trade, 2014)
Export of seafood needs utmost care from the beginning of the production process because it is the food which is exported for the consumption of the human beings. In Tamilnadu seafood exporters are very interested to involve in the seafood business, it is mainly for the reason of the resources acquisition through inland and marine sources and long coastal line. But in the coin, another side of this business it was face serious hurdle from the starting point of the business such as in infrequent supply of the raw materials due to mismatching demand between the production and export demand of seafood, low unit value realization of the major item in the export basket, obtaining license from the export inspection council and so on. In this research the researcher has used the mean, standard deviation, co variance, growth rate, compound annual growth rate, Pearson correlation analysis and so on. Through this study correlation analysis found that the there is a relationship exist between the quantity supplied and value of the seafood in the international market. The researcher concluded that seafood production has achieved better level and also demand is high in the international market but in the supply side of the export, seafood export quantity is supplied to the international market is changed based on the reason of unfavorable prices in the international market and wastage of the majority of the fisheries sources due to the improper cold storage.